Vertex Labeled Energy of Edge-Removed Complete Graphs - Nursyahida, Salwa; Rana, Salsabiil; Sukaesih, Esih (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2023)
Suppose Γ is vertex labeled graph by its degree. The (i,j)-th entry of vertex labeled matrix of Γ is label sum of different vertices v_i and v_j if there are paths between them, and 0 otherwise. Vertex labeled energy of Γ is absolute sum of its vertex labeled matrix eigenvalues. In this paper, we provide value of vertex labeled energy of edge-removed complete graph.